2020 IEEE Photonics Conference (IPC) 2020
DOI: 10.1109/ipc47351.2020.9252420
|View full text |Cite
|
Sign up to set email alerts
|

Size-Dependent Characterization of Deep UV Micro-Light-Emitting Diodes

Abstract: Deep UV Micro LEDs (DUV-µLEDs) are attractive for optical wireless communications, however not much is known about their size-dependent characteristics. Here we study spectra, power output and bandwidth as a function of device size and achieve a bandwidth of 570MHz with a 20µm diameter device.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 5 publications
(6 reference statements)
0
4
0
Order By: Relevance
“…24) To-date, the highest reported modulation bandwidth for a DUV LED is 570 MHz and was enabled by a single 20 μm diameter AlGaN micro-LED with a peak LOP of 130 μW. 25) Despite the reduced emission area for AlGaN-based micro-LEDs, the brightness (W cm -2 ) is remarkably enhanced due to their efficient light generation at kA cm -2 -level current densities enabled by a superior removal of the self-generated heat from the device active region. 21) At these levels of injection current density, the dynamic carrier lifetimes which chiefly dictate the maximum modulation bandwidth for micro-LEDs is also significantly reduced.…”
mentioning
confidence: 99%
“…24) To-date, the highest reported modulation bandwidth for a DUV LED is 570 MHz and was enabled by a single 20 μm diameter AlGaN micro-LED with a peak LOP of 130 μW. 25) Despite the reduced emission area for AlGaN-based micro-LEDs, the brightness (W cm -2 ) is remarkably enhanced due to their efficient light generation at kA cm -2 -level current densities enabled by a superior removal of the self-generated heat from the device active region. 21) At these levels of injection current density, the dynamic carrier lifetimes which chiefly dictate the maximum modulation bandwidth for micro-LEDs is also significantly reduced.…”
mentioning
confidence: 99%
“…A increases and then n(IQE peak) increases [28]. But the differences between the size-dependent J(EQE peak) are not large compared with the existing report [19], demonstrating the sidewall defect effect is not significant in this work. The wall-plug efficiency (WPE) versus current density for the UV-C LEDs are shown in figure 3(b).…”
Section: Resultsmentioning
confidence: 52%
“…In addition, the size effect on characteristics of UV-C micro-LEDs was also applied in deep-ultraviolet communications [17,18]. However, quantitative analyses and simulations of the mechanism for the size effect on efficiency and characteristics of UV-C micro-LEDs have not been adequately reported in literature, despite deserving far more research effort [19].…”
Section: Introductionmentioning
confidence: 99%
“…This has been attributed to smaller micro-LEDs being able to sustain higher operating current densities, in turn leading to shorter carrier recombination times and faster modulation responses. A size-dependent study on UVC micro-LEDs by Maclure et al [66] showed that this behavior is also observed in UV micro-LEDs. Fig.…”
Section: A Optical Communicationmentioning
confidence: 91%